2015
DOI: 10.3390/atmos7010001
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Character of Extreme Aerosol Events in the Southwestern United States: A Case Study Analysis in Arizona

Abstract: This study uses more than a decade’s worth of data across Arizona to characterize the spatiotemporal distribution, frequency, and source of extreme aerosol events, defined as when the concentration of a species on a particular day exceeds that of the average plus two standard deviations for that given month. Depending on which of eight sites studied, between 5% and 7% of the total days exhibited an extreme aerosol event due to either extreme levels of PM10, PM2.5, and/or fine soil. Grand Canyon exhibited the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 45 publications
(41 reference statements)
2
18
0
Order By: Relevance
“…However, high NDVI values suggest that there should be suppressed dust emissions due to more vegetation (Indoitu et al, 2015; Lopez et al, 2015). Aside from NDVI, other environmental parameters in Table S1 did not exhibit anomalously different values in July of 2003.…”
Section: Resultsmentioning
confidence: 99%
“…However, high NDVI values suggest that there should be suppressed dust emissions due to more vegetation (Indoitu et al, 2015; Lopez et al, 2015). Aside from NDVI, other environmental parameters in Table S1 did not exhibit anomalously different values in July of 2003.…”
Section: Resultsmentioning
confidence: 99%
“…16 This limit value for short-term PM 10 concentrations is often exceeded in various cities across Europe, Asia, and the United States. [17][18][19] In terms of exposure duration, a previous study 11 has shown distinct differences in results between rabbits that underwent TiO 2 instillation in the eye for 4 days and rabbits that underwent a single instillation of TiO 2 in the eye.…”
Section: Microparticle Exposure and Study Groupsmentioning
confidence: 97%
“…They found a teleconnection between Sahel precipitation and exogenous (i.e., Saharan) dust emissions resulted from an increase in Saharan wind speed in years of above average Sahel precipitation. In addition to regional factors, long range transport of dust and other emissions such as from fires can also significantly impact surface dust levels in areas thousands of kilometers downwind (e.g., Crosbie et al, 2014; Lopez et al, 2016). …”
Section: Introductionmentioning
confidence: 99%